"Drunken Boat": Samuel Beckett's Translation of Arthur Rimbaud's "Le Bateau ivre" - Gerald M. Macklin (Studies in 20th & 21st Century Literature, 2003)
This paper scrutinizes Samuel Beckett's translation of Arthur Rimbaud's famous poem "Le Bateau ivre." After a short introductory section which outlines how Beckett's translation fortuitously reached the public domain through the endeavors of James Knowlson and Felix Leakey and then raises some of the main issues arising from this encounter between two such celebrated authors, the article proceeds to offer a close analysis of the Beckett text in terms of Rimbaud's original. This involves a stanza-by-stanza consideration of the original and the translation as reproduced by Knowlson and Leakey and a suggested division of the two texts into four sections for the purposes of close examination. The paper attempts to bring out both the accuracy and the fidelity of Beckett's work but equally the majesty and ingenuity of the "translation" that he has produced. While his work reveals many fascinating insights into both the Rimbaldian aesthetic and the Beckettian, ultimately one is struck by the fact that Beckett has produced something that goes far beyond what we originally designate as a "translation." "Drunken Boat" emerges as a poem in its own right as well as a staggeringly successful rendering of a poem that has so often resisted satisfactory translation.
Keywords: Samuel Beckett; translation; Arthur Rimbaud; Le Bateau ivre; public domain; James Knowlson; Felix Leakey; close analysis; stanza-by-stanza; original; accuracy; fidelity; Rimbaldian aesthetic; Beckettian; Drunken Boat